Shaking Table Test on the Seismic Responses of a Slope Reinforced by Prestressed Anchor Cables and Double-Row Antisliding Piles - Zuo-ju Wu; Zhi-jia Wang; Jun-wei Bi; Xiao Fu; Yong Yao (Shock and Vibration)
The combined retaining structure has gradually received considerable attention in the slope engineering, due to its good reinforcement effects. However, most of the published research studies were focused on the seismic responses of the single-formal supporting structure only. The investigations of dynamic responses of the combined retaining structures are scarce, and the current seismic design is conducted mainly based on experiences. In this work, a series of large-scale shaking table tests were conducted to investigate the seismic responses of the combined retaining structures (i.e., prestressed anchor cables and double-row antisliding piles) and the reinforced slope under seismic excitations, including amplification effect of internal and surface acceleration of the reinforced slope, distribution and change of prestress of the anchor cable, dynamic response of soil pressure behind the antislide pile, and horizontal displacement of the reinforced slope surface. Test results show that, supported by the reinforcement of composite support system, the slope with the multilayer weak sliding surface can experience strong ground motion of 0.9 g. The load of the antisliding pile has reached 80% of its bearing capacity, and the load of the anchor cable has reached 75.0% of its bearing capacity. When the seismic intensity reaches 0.5 g, the slope surface has an obvious downward trend, which will make the corresponding soil pressure suddenly increase after the antislide pile. At the potential sliding zone, the axial force of the anchor cable will increase suddenly under the action of earthquake; after the earthquake, the initial prestress of the anchor cable will be lost, with the loss range of 17.0%∼23.0%. These test results would provide an important reference for the further study of the seismic performance of such composite support structure.